Alterations of the Adipo–Myokine Irisin in Sepsis and Septic Shock: Diagnostic and Prognostic Implications - Irene Karampela; Natalia G. Vallianou; Dimitrios Tsilingiris; Gerasimos Socrates Christodoulatos; Sotiria Psallida; Dimitris Kounatidis; Theodora Stratigou; Ioanna Marinou; Evaggelos Vogiatzakis; Maria Dalamaga (Biomolecules, 2024)
Irisin, a novel adipo-myokine with metabolic regulatory functions, exerts anti-inflammatory, antioxidant, and anti-apoptotic actions that may confer protection against sepsis-induced organ injury in experimental studies. Until now, only one human study has explored circulating irisin at sepsis onset. We aimed to examine serum irisin and its kinetics in critically ill patients with sepsis and septic shock with regard to sepsis severity and outcome. We enrolled 102 critically ill patients with sepsis or septic shock within 48 h of diagnosis and 102 age- and gender-matched healthy controls. Irisin was determined in serum upon enrollment in all participants and one week later in patients using an immunoenzymatic method. The outcome of sepsis was recorded 28 days after enrollment. At enrollment, circulating irisin was significantly lower in patients than controls (22.3 ± 6.8 μg/L vs. 28.1 ± 6.7 μg/L, p < 0.001), and increased significantly one week later (22.3 ± 6.8 μg/L vs. 26.6 ± 9.5 μg/L, p < 0.001). Irisin was significantly lower in patients who presented with septic shock than those with sepsis, and in non-survivors than survivors both at enrollment and one week later. However, kinetics of irisin did not differ between the groups (p > 0.05). Patients with higher circulating irisin during the first week of sepsis had a better outcome (p < 0.001). Lower irisin was independently associated with 28-day mortality (sepsis onset: HR 0.44, 95% C.I. 0.26–0.77, p = 0.004 and one week after: HR 0.37, 95% C.I. 0.23–0.58, p < 0.001). Irisin was negatively correlated with severity scores, metabolic, and inflammatory biomarkers. Circulating irisin decreases early in sepsis and is an independent predictor of 28-day mortality. Irisin may be a promising diagnostic and prognostic sepsis biomarker; nevertheless, larger studies are needed to explore its role in sepsis.